If it's not what You are looking for type in the equation solver your own equation and let us solve it.
6(m-2)+14=3(m+12)-10
We move all terms to the left:
6(m-2)+14-(3(m+12)-10)=0
We multiply parentheses
6m-(3(m+12)-10)-12+14=0
We calculate terms in parentheses: -(3(m+12)-10), so:We add all the numbers together, and all the variables
3(m+12)-10
We multiply parentheses
3m+36-10
We add all the numbers together, and all the variables
3m+26
Back to the equation:
-(3m+26)
6m-(3m+26)+2=0
We get rid of parentheses
6m-3m-26+2=0
We add all the numbers together, and all the variables
3m-24=0
We move all terms containing m to the left, all other terms to the right
3m=24
m=24/3
m=8
| -3u+18=-8u+51 | | 3p/7-19=-13 | | (n^2-9n-5)=0 | | (x/5)+(x-1/3)=2 | | 2p−p=7 | | x^2-x/15-2/5=0 | | -18h+9=-19h | | -4(4w-3)+2w=4(w+5) | | 4/3w=28 | | 8=-4(-3+c) | | 11a−5a=18 | | 9^x+3=5x | | 7x+7/10=28 | | 1.75x-132.49=369.76 | | 8=−4(−3+c) | | $1.75x-$132.49=$369.76 | | 3(u-8)-6=-3(-9u+6)-8u | | 13q-8q+1=11 | | 5+8b=29 | | x32=1.5 | | 184=-8(7+4y) | | 3v+5=24 | | 8h-5h=9 | | 11w+66=-71 | | x/12=68 | | -16x^2-33x-16=0 | | 7n-35=2n+26 | | 16-2n=-8+4(1n-3) | | 3(x+4)-2(x+1=0 | | 7-3x+8x=2 | | q=16÷4 | | -16+11=h |